Analysis of the Influence of Brand Image, Product Quality, and Price on Consumer Purchase Interest - Rosadi, Farhan Budi; Kusdiyanto, Kusdiyanto (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Competition in the business world is increasingly fierce, making companies try to find fast and appropriate strategies in marketing their products. The aim of this research is to analyze the influence of brand image, product quality and price on purchasing interest among Matahari department store Surakarta consumers. This type of research uses quantitative methods. The data used in this research is primary data. Data collection in this research was carried out by distributing questionnaires. This research uses a purposive sampling technique. The sampling method in this research used 200 respondents. Data analysis methods in processing data and drawing conclusions, researchers use computer assistance through the SPSS program. The results of this research are that brand image has a significant effect on consumer buying interest. The large influence of brand image shows that consumers, apart from looking at the brand, also see other factors such as price, product quality and other factors that influence buyer interest. Product quality has a positive and significant effect on consumer buying interest. This shows that the better the product quality, the more consumer buying interest will increase. Price has a positive and significant effect on consumer buying interest. In this case, the need for competitive product prices will increase interest in purchasing the product itself.